Design, construction and evaluation of a refrigeration system for the sp150p photovoltaic panel (Revista Cientifica Ingenio Magno, 2020)
With the need to reduce dependence on fossil fuels, photovoltaic solar panel technology hasbeen widely developed, with affordable prices on the market. Colombia has great solar potential to generate electrical energy through solar panels. Inherent in its operation is the drawback of raising its temperature, which affects its functionality. The objective of this work was: to evaluate a refrigeration system for a photovoltaic panel SP150P, installed on the roof of the Antonio Nariño University, in Tunja at the latitude of 5,553 degrees N and longitude W of 77,367 degrees. A statistical analysis of the temperatures initially recorded and stored was performed with the use of thermocouples placed at different points on the panel. The previous results allowed the sizing of the refrigeration system. Other variables, such as height, wind speed and geographic location of the panel, were also taken into account in the design. The flow regime was calculated using the Reynolds number and the heat transfer processes by conduction, convention and radiation from the panel to the heat exchanger, which allowed determining the necessary parameters of the solenoid valve that would control the flow by gravity from a tank placed at a height above the panel. These results demonstrate the feasibility of reducing the temperature of the solar panels and improving their efficiency, making it feasible to implement them at industrial levels or in other potential applications.
Keywords: Photovoltaic panel; cooling system; heat transfer; solar radiation